Evaluation of a Miniature Ge-Doped Silica Optical Fiber Radioluminescence Dosimeter for Absolute Dose Measurement in a 6 MeV Electron Radiotherapy Beam (Bangladesh Journal of Medical Physics, 2025)
In radiotherapy, absolute dosimetry has traditionally relied on ionization chambers, which provide high accuracy but are relatively bulky and expensive. But in contrast, miniaturized radioluminescence (RL) detectors present a promising alternative, offering compact size, real-time readout, and reduced cost. This study aims to evaluate the dosimetric performance of a Ge-doped silica optical fiber ((SiO2:Ge), with dimensions of 1 mm in diameter and 1 mm in length, as a radioluminescence (RL) detector for absolute dose measurements in a 6 MeV electron beam generated by a Varian Clinac-iX linear accelerator. A SiO2:Ge was coupled to a 1 mm silica optical fiber and positioned at a depth of 2.4 cm in a water-equivalent bolus, corresponding to the R50 for 6 MeV electrons, with a source-to-surface distance (SSD) of 100 cm. Irradiations were delivered using a Varian Clinac-iX at a dose rate of 400 MU/min under controlled room conditions (20°C, 101320 Pa). The RL signal was transmitted via the optical fiber to a myDoz® RL/OSL dosimetry system, which recorded the emitted photon counts. Calibration was carried out with reference doses of 1 Gy and 5 Gy, and the response was subsequently validated at 2 Gy. With the SiO2:Ge in place, photon counts of 22340 and 111413 were recorded at 1 Gy and 5 Gy, respectively, while corresponding measurements without the crystal yielded 20017 and 99832 counts. Linear calibration predicted counts of 44608 (with sample) and 39,971 (without sample) for a 2 Gy exposure. The experimentally measured values of 44539 and 39940 differed from the predictions by less than 0.3%, thereby confirming the excellent linearity of the detector response. This 1 mm × 1 mm Ge-doped silica optical fiber RL dosimeter demonstrated a highly accurate and linear dose response in 6 MeV electron beam irradiation. This study reveals that its sensitive volume is smaller than that of conventional ionization chambers, the detector presents a promising, low-cost approach for small-field and in vivo dosimetry.Ban. J. Med. Phys., Vol -16, Issue -2, 2025 : 73-76